Systematic Literature Review Regarding Opportunities, Challenges and Effectiveness in Financial Reporting of Public Service Agencies (BLUD) in the Province, Sumatera Utara - Putri Kesha Abelia; Kesya Aulia Ramadhani Daulay; Sayidina Aditya Prayogi; Iskandar Muda; Andy Mulia (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to present a Systematic Literature Review by analyzing the opportunities and challenges regarding the financial reports of regional public service agencies (BLUD) in North Sumatra Province using secondary research methods aimed at obtaining critical and structural research results. The main focus of this study is to uncover the opportunities and challenges in financial reporting by implementing government accounting standards. A systematic literature review was conducted by synthesizing the results of published research by taking the theoretical framework as a reference for writing this research. The results of the synthesis indicate that the opportunities in implementing Regional Public Service Agencies (BLUD) in North Sumatra lie in the flexibility of financial resource management in BLUD by continuously striving to improve public services in providing results regarding the flexibility of patterns in regional financial management of Regional Public Service Agencies (BLUD). There are also very significant challenges regarding financial reporting in North Sumatra, namely the gap in human resource competency related to the implementation of government accounting standards by measuring the limitations of the integration of Accounting information systems. In general, this research method is implemented to achieve opportunities and resolve challenges in the financial reporting of Regional Public Service Agencies (Regions) and optimize the final results of regional financial reports.